2011
DOI: 10.4327/jsnfs.64.393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foods on Antitumor Activity of Doxorubicin, Melphalan and Methotrexate

Abstract: Recently, with increasing interest in the cancer-preventive effects of complementary and alternative medicine CAMs including functional foods and herbs, their use as health foods has been increasing among cancer patients. Although the antitumoral or cytotoxic activities of CAMs have been well examined, little is known about possible interactions between foods used as CAMs and chemotherapeutic agents. Therefore, in the present study, the effects of ethyl acetate extracts of eight foods or herbs commonly used by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…1,2) Moreover, undesirable pharmacokinetic or pharmacodynamic interactions have been reported with various drugs. [3][4][5][6][7] We also demonstrated that kurosu (Japanese unpolished rice vinegar) is capable of modulating the intestinal absorption of P-glycoprotein (P-gp) substrates. 8) Accordingly, further accumulation of information about clinically relevant interactions between drugs and various kinds of health foods is required.…”
mentioning
confidence: 99%
“…1,2) Moreover, undesirable pharmacokinetic or pharmacodynamic interactions have been reported with various drugs. [3][4][5][6][7] We also demonstrated that kurosu (Japanese unpolished rice vinegar) is capable of modulating the intestinal absorption of P-glycoprotein (P-gp) substrates. 8) Accordingly, further accumulation of information about clinically relevant interactions between drugs and various kinds of health foods is required.…”
mentioning
confidence: 99%